Selective trimerization of α-olefins with immobilized chromium catalyst for lubricant base oils - Baek, Jun Won; Hyun, Young Bin; Lee, Hyun Ju; Lee, Jong Chul; Bae, Sung Moon; Seo, Yeong Hyun; Lee, Dong Geun; Lee, Bun Yeoul (Catalysts, 2020)
The demand for poly(α-olefin)s (PAOs), which are high-performance group IV lubricant base oils, is increasingly high. PAOs are generally produced via the cationic oligomerization of 1-decene, wherein skeleton rearrangement inevitably occurs in the products. Hence, a transition-metal-based catalytic process that avoids rearrangement would be a valuable alternative for cationic oligomerization. In particular, transition-metal-catalyzed selective trimerization of α-olefins has the potential for success. In this study, (N,N′,N”-tridodecyltriazacyclohexane)CrCl3 complex was reacted with MAO-silica (MAO, methylaluminoxane) for the preparation of a supported catalyst, which exhibited superior performance in selective α-olefin trimerization compared to that of the corresponding homogeneous catalyst, enabling the preparation of α-olefin trimers at ~200 g scale. Following hydrogenation, the prepared 1-decene trimer (C30H62) exhibited better lubricant properties than those of commercial-grade PAO-4 (kinematic viscosity at 40◦C, 15.1 vs. 17.4 cSt; kinematic viscosity at 100◦C, 3.9 vs. 3.9 cSt; viscosity index, 161 vs. 123). Moreover, it was shown that 1-octene/1-dodecene mixed co-trimers (i.e., a mixture of C24H50, C28H58, C32H66, and C36H74), generated by the selective supported Cr catalyst, exhibited outstanding lubricant properties analogous to those observed for the 1-decene trimer (C30H62).
Keywords: Chromium; Lubricant base oil; Selective α-olefin trimerization; Supported catalyst